"Hit and run" therapy averts macular degeneration - Bubeck, Felix; Grimm, Dirk (Nature biomedical engineering, 2021)
Subretinal delivery of lentiviruses bearing Cas9 mRNA and a guide RNA targeting the Vegfa gene reduces the development of choroidal neovascularization in a mouse model of wet age-related macular degeneration.
Gesehen am 01.12.2021